2014
DOI: 10.1534/genetics.113.159210
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Link Between Notch Signaling and ROS in Restricting the Differentiation of Hematopoietic Progenitors in Drosophila

Abstract: A fundamental question in hematopoietic development is how multipotent progenitors achieve precise identities, while the progenitors themselves maintain quiescence. In Drosophila melanogaster larvae, multipotent hematopoietic progenitors support the production of three lineages, exhibit quiescence in response to cues from a niche, and from their differentiated progeny. Infection by parasitic wasps alters the course of hematopoiesis. Here we address the role of Notch (N) signaling in lamellocyte differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 72 publications
4
68
0
Order By: Relevance
“…Thus, we suggest that the PSC does not function as a niche required for blood cell progenitor maintenance. Several lines of evidence supporting the niche function of the PSC are based on ectopic or overexpression of various proteins in the PSC to alter its size and activity (11,13,15,17,21,29). These manipulations may not always reflect the real function of the PSC as they can cause sustained activation of abnormal programs that indirectly impinge on prohemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that the PSC does not function as a niche required for blood cell progenitor maintenance. Several lines of evidence supporting the niche function of the PSC are based on ectopic or overexpression of various proteins in the PSC to alter its size and activity (11,13,15,17,21,29). These manipulations may not always reflect the real function of the PSC as they can cause sustained activation of abnormal programs that indirectly impinge on prohemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased levels of ROS have induced the differentiation of hematopoietic stem cells in Drosophila and mammals (21,22). In Drosophila, high ROS levels were detected in hematopoietic progenitor cells, and increased ROS levels were detected in the posterior signaling center of the lymph gland after a wasp infestation (23). In the fly, ROS serve as an important signal for progenitor cell differentiation into lamellocytes, a hemocyte type that encapsulates wasp eggs (24,25).…”
mentioning
confidence: 99%
“…Infection by parasitoid wasps also results in proliferation of lamellocytes in the larval lymph gland. Unexpectedly, Small et al (2014) found that Notch signaling regulates this lamellocyte differentiation. It appears that Notch signaling acts in a non-cell-autonomous manner in the lymphatic organ to hold lamelloctye precursor cells in quiescence, but inhibition of Notch by RNAi or parasitoid infection allows lamellocyte differentiation to proceed.…”
Section: Complex Regulation Of Immunitymentioning
confidence: 94%
“…Tiller and Garsin (2014) identified a novel peroxidase, skpo1, that controls ROS production in the C. elegans hypodermal epithelia and correspondingly determines defense against infection by the bacterium Enterococcus faecalis. Small et al (2014) found an unexpected pleiotropy between ROS production and immune cell differentiation mediated by Notch signaling in Drosophila. Notch signaling promotes the embryonic differentiation of crystal cells, which are responsible for ROS production in larvae attacked by parasitoid wasps.…”
Section: Complex Regulation Of Immunitymentioning
confidence: 94%